Phytochemicals as a Complement to Cancer Chemotherapy: Pharmacological Modulation of the Autophagy-Apoptosis Pathway - Rahman, Md. Ataur; Hannan, Md. Abdul; Dash, Raju; Rahman, MD. Hasanur; Islam, Rokibul; Uddin, Md Jamal; Sohag, Abdullah Al Mamun; Rahman, Md. Habibur; Rhim, Hyewhon (Frontiers in Pharmacology, 2021)
Phytochemicals, a class of well-known bioactive plant derived compounds with a wide range of therapeutic applications, are constituents of traditionally used herbal medicines that display promising anticancer properties. Further evidence suggests that phytochemicals modulate autophagy and apoptosis, the two crucial cellular pathways involved in the underlying pathobiology of cancer development and regulation. Pharmacological targeting of autophagy and apoptosis signaling using phytochemicals therefore offers a promising strategy that is complementary to conventional cancer chemotherapy. In this review, we sought to highlight the molecular basis of the autophagic-apoptotic pathway to understand its implication in the pathobiology of cancer, and explore this fundamental cellular process as a druggable anticancer target. We also aimed to present recent advances and address the limitations faced in the therapeutic development of phytochemical-based anticancer drugs.